Spatial and directional control over self-assembly using catalytic micropatterned surfaces - Alexandre G. L. Olive; Nor Hakimin Abdullah; Iwona Ziemecka; Eduardo Mendes; Rienk Eelkema; Jan H. Van Esch (2014)
Catalyst-assisted self-assembly is widespread in nature to achieve spatial control over structure formation. Reported herein is the formation of hydrogel micropatterns on catalytic surfaces. Gelator precursors react on catalytic sites to form building blocks which can self-assemble into nanofibers. The resulting structures preferentially grow where the catalyst is present. Not only is a first level of organization, allowing the construction of hydrogel micropatterns, achieved but a second level of organization is observed among fibers. Indeed, fibers grow with their main axis perpendicular to the substrate. This feature is directly linked to a unique mechanism of fiber formation for a synthetic system. Building blocks are added to fibers in a confined space at the solid–liquid interface.